Open Reduction and Internal Fixation of Displaced Supracondylar Fracture of Humerus in Children: Comparison Between Lateral and Medial Approach - Mushtaq, Zunair; Mehmood, Mazhar; Javid, Afzal; Hassan, A R; Habib, Khurram; Ahmed, Imran (Indus Journal of Bioscience Research, 2025)
Objective: To compare the functional outcomes and ulnar nerve injury rates between the lateral and medial approaches for ORIF in displaced supracondylar fractures of the humerus in children. Study Settings: This randomized controlled trial was conducted at the Department of Orthopedic Surgery, Allied-II Hospital, Faisalabad. Duration of Study: The study was conducted over six months from 10 August 2024 to 10th Feb 2025 and following the approval of the synopsis. Methodology: A total of 410 children aged 3–14 years with Gartland Types I–III supracondylar fractures were randomly assigned to two groups: Group A (medial approach, n=205) and Group B (lateral approach, n=205). Patients with congenital bone diseases, delayed presentation (>6 days post-injury), or neurovascular compromise were excluded. All procedures were performed under general anesthesia by experienced consultants. Functional outcomes were assessed using Flynn’s criteria, and ulnar nerve injury rates were compared. Data were analyzed using SPSS v25.0, with p ≤ 0.05 considered significant. Results: The incidence of ulnar nerve injury was significantly higher in Group A (2.4%) compared to Group B (0%) (p=0.024). Both approaches demonstrated comparable functional outcomes, with 90.4% and 88.09% satisfactory results in the lateral and medial groups, respectively. BMI (11–18) was significantly associated with ulnar nerve injury (p=0.028). Complications, including superficial pin tract infections, were minimal and resolved with standard care. Conclusion: The lateral approach is a safer and equally effective alternative to the medial approach for ORIF in pediatric supracondylar fractures, with a lower risk of ulnar nerve injury and comparable functional outcomes. Surgeon expertise and patient-specific factors should guide the choice of surgical approach.